Extensive tip-splitting of injected organic liquid into an aqueous viscoelastic fluid - Yoshii, Kiwamu; Otoguro, Kojiro; Sato, Ayane Pygoscelis; Sumino, Yutaka (Frontiers in Physics, 2024)
The injection of a fluid into another fluid causes a spatiotemporal pattern along the injection front. Viscous fingering is a well-known example when the replaced material is a viscous fluid.Notably, most fluids are, in reality, viscoelastic, i.e., they behave as an elastic solid over short timescales. For this reason, it is important to study the situation when the replaced fluid is viscoelastic. In this study, we observe extensive tip-splitting in the fingering pattern when an incompressible organic liquid was injected into an oleophilic Hele-Shaw cell filled with an aqueous viscoelastic fluid made of a wormlike micellar solution. The tip-splitting led to thin fingers with a characteristic size comparable to four times the cell thickness. We examined the material properties and suggest that the thin fingering pattern observed in our current system is due to the delamination of viscoelastic fluid from the bottom substrate surface. Our result shows that the effect of interfacial energy in the existing solid layer should be considered in the injection process.